2007
DOI: 10.1063/1.2790433
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption, desorption, and diffusion of nitrogen in a model nanoporous material. II. Diffusion limited kinetics in amorphous solid water

Abstract: The adsorption, desorption, and diffusion kinetics of N2 on thick (up to approximately 9 microm) porous films of amorphous solid water (ASW) films were studied using molecular beam techniques and temperature programmed desorption. Porous ASW films were grown on Pt(111) at low temperature (<30 K) from a collimated H2O beam at glancing incident angles. In thin films (<1 microm), the desorption kinetics are well described by a model that assumes rapid and uniform N2 distribution throughout the film. In thicker fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 41 publications
0
38
1
Order By: Relevance
“…This indicates that the ratio between 3and 4-coordinated water molecules is more or less a constant. As the properties of ASW surface is determined by the relative ratio between 2-, 3-, and 4-coordinated water molecules, this would indicate that other than the differing in the total pore surface area, the properties of the pore surface remain the same between 60 and 140 K. Previously, Zubkov et al (2007) performed TPD measurements of N 2 adsorbed on both compact and porous ASW, and found that if a correction for surface area is taken into account, the desorption energy distribution on porous ASW is nearly identical to that of compact ASW. Our results based on a different method agrees with their conclusion.…”
Section: Discussion and Astrophysical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the ratio between 3and 4-coordinated water molecules is more or less a constant. As the properties of ASW surface is determined by the relative ratio between 2-, 3-, and 4-coordinated water molecules, this would indicate that other than the differing in the total pore surface area, the properties of the pore surface remain the same between 60 and 140 K. Previously, Zubkov et al (2007) performed TPD measurements of N 2 adsorbed on both compact and porous ASW, and found that if a correction for surface area is taken into account, the desorption energy distribution on porous ASW is nearly identical to that of compact ASW. Our results based on a different method agrees with their conclusion.…”
Section: Discussion and Astrophysical Implicationsmentioning
confidence: 99%
“…This happens at a higher CO dose than the full covering of the dOH bonds, likely because CO molecules preferentially occupy the dOH sites than non-dOH sites. In a prior study by Zubkov et al (2007), it is reported that the full coverage of pore surface by nitrogen adsorption happens simultaneously with the saturation of the shifted dangling bond intensity. They suggested that N 2 does not preferentially bind to dangling OH groups.…”
Section: Modelingmentioning
confidence: 92%
“…21 The coefficients s i and D i , are functions of and T. In our study with methane we analyzed the equilibrium isotherms with the condensation approximation, 22 where D = 0 for sites with binding energy above a value 0 ͑P , T͒, and infinity for sites with Ͻ 0 ͑P , T͒. The adsorbed molecules migrate rapidly by surface diffusion 5,23 and stick to the strongest available binding sites, and one can define N M , a maximum value of N below which nearly all the occupied sites have binding energies higher than 0 ͑P , T͒ ͑hence D =0͒. Therefore, the desorption term can be dropped from Eq.…”
Section: Discussionmentioning
confidence: 99%
“…As a typical porous and structurally dynamic material, ASW is very sensitive to the substrates' temperature. 18,39 It plays a crucial role since the packing of the water molecules is rather sensitive to the temperature, causing defects diffusion by water molecules reorientation 20, 40 at ≈105 K, followed by more packed ASW films at 135 K ± 15 K, i.e., tighter structure of the frozen water film, up to full crystalline ice formation at 155 K. The effect of ASW layer annealing temperature prior to MeCl adsorption on its overall sticking probability and subsequent desorption uptake is demonstrated in Fig. 1(b).…”
Section: A Tpd Of "On-top" and Caged Methyl Chloride Molecules From Aswmentioning
confidence: 99%